IMPLEMENTASI STRATEGI DINAS TENAGA KERJA KABUPATEN INDRAGIRI HULU (STUDI KASUS PADA PENYELESAIAN PERMASALAHAN PENGUPAHAN) - Nur Indah Sari; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Wages are rights of workers or laborers that are received and declared as compensation from employers or employers to workers which are determined and paid according to an employment agreement, agreement, or regulation. The wage policy in Indragiri Hulu Regency which is manifested in the Regency Minimum Wage (UMK) is a manifestation of the role of the local government in industrial relations, but still causes many problems and violations. Therefore, the Manpower Office of Indragiri Hulu Regency must implement the right strategy to overcome the wage problem. The purpose of this research is to determine the Implementation of the Strategy of the Manpower Office in Overcoming Wage Problems in Indragiri Hulu Regency and to find out the factors that hinder the Implementation of the Strategy of the Manpower Office in Overcoming Wage Problems in Indragiri Hulu Regency. This study uses the theory of J. David Hunger and Thomas L. Wheelen (2003: 27-28), which uses indicators, namely: program, budget, procedures. This research uses qualitative methods and documentation. The results of this study indicate that: first, the implementation of the strategy of the Manpower Office of Indragiri Hulu Regency in overcoming the wage problem has not been maximally proven by the fact that there are still companies that do not pay wages to workers who are not in accordance with the rights that must be received. Second, the inhibiting factor is the limited human resources and facilities and infrastructure in the form of transportation to support the decline in space. Keywords: Implementation, Strategy, Wages